Approximation by trigonometric polynomials in weighted grand Lorentz spaces - Jafarov, S.Z. (Romanovsky Institute of Mathematics of the Academy of Sciences of the Republic of Uzbekistan, 2024)
In the present paper, the relationship between the best approximation of the function and the best approximation of the derivatives of the function in the weighted grand Lorentz spaces has been investigated. The best approximation of the functions by trigonometric polynomials in weighted grand Lorentz spaces is studied. We study the inverse problem of approximation theory in weighted grand Lorentz spaces. © 2024, Romanovsky Institute of Mathematics of the Academy of Sciences of the Republic of Uzbekistan. All rights reserved.
Keywords: best approximation; Moduli of smoothness; Muckenhoupt weight; trigonometric approximation; weighted grand Lorentz spaces